2022
DOI: 10.1002/slct.202103869
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Surface Oxygen Defects on ZnO/ZnS Catalysts to Promote Photocatalytic H2 Production

Abstract: Zinc oxide/zinc sulfide (ZnO/ZnS) microparticles with enriched surface oxygen defects (D so ) were prepared via a hydrothermal sulfurization modulated by doping sliver/copper ions (Ag + / Cu 2 + ). Microsized ZnO precursors with different structures were firstly prepared in the presence of Ag + /Cu 2 + . A subsequent surface sulfurization of the precursor led to the formation of ZnS nanostructure, forming ZnO/ZnS with modulated D so simultaneously. In addition, this in-situ sulfurization ensured the homogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[9][10][11][12] However, the photocatalytic efficiency of ZnO is limited owing to its wide bandgap, low utilization of sunlight, and rapid recombination of photogenerated electrons and holes. [13][14][15][16][17] Many studies have shown that the photocatalytic performance of ZnO can be improved by noble metal deposition, [18,19] metal ion doping, [20][21][22] and heterojunction fabrication. [23][24][25] Among them, the construction of heterojunction is considered the simplest and most effective method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] However, the photocatalytic efficiency of ZnO is limited owing to its wide bandgap, low utilization of sunlight, and rapid recombination of photogenerated electrons and holes. [13][14][15][16][17] Many studies have shown that the photocatalytic performance of ZnO can be improved by noble metal deposition, [18,19] metal ion doping, [20][21][22] and heterojunction fabrication. [23][24][25] Among them, the construction of heterojunction is considered the simplest and most effective method.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is one of the most widely investigated semiconductor photocatalysts because of its chemical stability, nontoxicity, and low cost [9–12] . However, the photocatalytic efficiency of ZnO is limited owing to its wide bandgap, low utilization of sunlight, and rapid recombination of photogenerated electrons and holes [13–17] . Many studies have shown that the photocatalytic performance of ZnO can be improved by noble metal deposition, [18,19] metal ion doping, [20–22] and heterojunction fabrication [23–25] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the higher content of Mo 3+ means the higher oxygen vacancy content. [29][30][31] Fig. 3d shows the highresolution O 1s spectra of MnO x /MnWO 4 @C-3 composites, which reveal three typical peaks at 530.87, 532.37 and 530.35 eV, representing lattice oxygen (O1), oxygen vacancy (O2) and oxygen species adsorbed on the surface (O3), respectively.…”
Section: Resultsmentioning
confidence: 99%